GRADE Methods in traditional medicine - Jian-Ping Liu (Integrative Medicine Research)
The GRADE (Grading of Recommendation, Assessment, Development and Evaluation) methods was developed to evaluate the quality of evidence and make recommendations, which has been widely adopted in clinical practice guidelines. The GRADE methods address the classification of outcomes, systematic collection, appraisal and synthesis of research evidence based on each outcome, evaluate the overall quality of the evidence, and making recommendations. This essay summarized the GRADE methods and its use in clinical practice guidelines of traditional, complementary, and integrative medicine as well as highlighting some of the challenges.